The RNA from Pseudomonas aeruginosa Reduces Neutrophil Responses Favoring Bacterial Survival - Jose R. Pittaluga; Federico Birnberg-Weiss; Agustina Serafino; Joselyn E. Castro; Luis A. Castillo; Daiana Martire-Greco; Paula Barrionuevo; Gabriela C. Fernández; Verónica I. Landoni (Karger Publishers, 2024)
Introduction: Epithelial and endothelial cells modulate innate immune responses in the lung, including the arrival of neutrophils (PMN), which are crucial cells for the antibacterial host defense. Cells are exposed to prokaryotic RNA (pRNA) during bacterial infections and different pRNA may promote or attenuate the inflammatory response on different immune cells. Pseudomonas aeruginosa (PAE) can cause severe pneumonia and has several immune-evading mechanisms. The aim of this study was to determine the effects of the RNA from PAE (RNAPAE) on lung epithelial, endothelial cells, and PMN, and its impact on bacterial elimination. Methods: Purified total RNAPAE was used as a stimulus on a human lung epithelial cell line (Calu-6), human microvascular endothelial cell line HMEC-1 and isolated healthy human PMN. Activation and cytokine secretion were evaluated. In addition, PMN elimination of live ECO or PAE was determined in the presence of RNAPAE. Results: We found that RNAPAE either induced a pro-inflammatory response on Calu-6 and HMEC-1 or PMN. Pre-stimulation of PMN with RNAPAE diminished activation and chemotaxis induced by live bacteria. Moreover, we found that RNAPAE reduced phagocytosis of live ECO. Finally, we also found that non-degraded fragments of small RNA (<200 bp) were responsible for the PMN microbicidal attenuation during PAE elimination. Conclusion: Our results indicated that short fragments of RNAPAE diminished the immune response of PMN favoring bacterial survival.